2019
DOI: 10.1111/ocr.12259
|View full text |Cite
|
Sign up to set email alerts
|

A novel nonsense substitution identified in the AMIGO2 gene in an Occulo‐Auriculo‐Vertebral spectrum patient

Abstract: Structured Abstract Objective Craniofacial microsmia is the second most common congenital disorder with mostly unilateral defects of ear, temporomandibular joint, mandible, and muscles of facial expression and mastication. The objective of this study was to identify, if there were any, de novo germline or somatic variants in a patient with Occulo‐Auriculo‐Vertebral Spectrum (OAVS) using whole‐exome sequencing. Settings and Sample Population Trio/Family‐based study of an OAVS proband. Materials and Methods Chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…However, it is not clear whether CMA can contribute to etiological diagnosis for all CFM patients. In fact, individuals presenting additional major features should be investigated by CMA, but for individuals with only features within the CFM spectrum, a multifactorial etiology is the most supported (Rengasamy Venugopalan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is not clear whether CMA can contribute to etiological diagnosis for all CFM patients. In fact, individuals presenting additional major features should be investigated by CMA, but for individuals with only features within the CFM spectrum, a multifactorial etiology is the most supported (Rengasamy Venugopalan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the patients from this study had a clinical diagnosis of Treacher Collins or any other syndromic diagnosis associated with CFM. Recently, mutations in other genes, including the MYT1 , ZIC3 , and AMIGO2 were described as a genetic cause of CFM (Lopez et al, 2016; Rengasamy Venugopalan et al, 2019; Trimouille et al, 2020). Nevertheless, for most CFM patients, the genetic cause remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, some studies reported discreet copy number variants or single nucleotide polymorphisms that might contribute to the features of the RCEM in question (Lombardi et al, 2011;Lopez et al, 2016;Rengasamy Venugopalan et al, 2019;Steiner, Vengoechea, & Collins 2nd., 2013). However, none of these have been recurrent across cohorts of affected individuals, suggesting that these are more likely to be either coincidental or predisposition rather than causal variants.…”
Section: Literature Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…A genetic origin of OAVS is supported by the description of familial forms, 2 along with the existence of several causative copy number variations, 3,4 and more recently the description of deleterious variants in MYT1 5,6 and AMIGO2 7 genes. However, pathogenic variants in known genes or copy number variations only explain a small number of OAVS cases, and the molecular basis of this spectrum remains elusive.…”
Section: Introductionmentioning
confidence: 99%